1994
DOI: 10.1099/00221287-140-10-2867
|View full text |Cite
|
Sign up to set email alerts
|

A numerical phenotypic taxonomic study of the genus Neisseria

Abstract: A numerical phenotypic taxonomic study of 315 strains of Neisseria and some allied bacteria examined for 155 phenotypic tests showed 31 groups, most of which were reasonably distinct. These fell into four major areas. Areas A, B and C contained species of Neisseria, whereas area D contained the organisms known as 'false neisserias' together with Branhamella, Moraxella and Kingella species. Area A contained N. gonorrhoeae (which showed two subgroups), N. meningitidis (with two subgroups, and N. cinerea closely … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
42
0

Year Published

2000
2000
2016
2016

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 59 publications
(44 citation statements)
references
References 44 publications
2
42
0
Order By: Relevance
“…It is possible that the genus Simonsiella had a monophyletic origin and that 16S rDNA evidence of the monophyly of the group was lost. Discrepancies abound between 16S rDNA phylogenies of the genus Neisseria and those derived from analyses of other loci (Smith et al, 1999) or from chemotaxonomic data (Barrett & Sneath, 1994). Smith et al (1999) suggested that the anomalies were due to interspecies gene exchange.…”
Section: Resultsmentioning
confidence: 99%
“…It is possible that the genus Simonsiella had a monophyletic origin and that 16S rDNA evidence of the monophyly of the group was lost. Discrepancies abound between 16S rDNA phylogenies of the genus Neisseria and those derived from analyses of other loci (Smith et al, 1999) or from chemotaxonomic data (Barrett & Sneath, 1994). Smith et al (1999) suggested that the anomalies were due to interspecies gene exchange.…”
Section: Resultsmentioning
confidence: 99%
“…The multidimensional space of phenotypic diversity can then be collapsed onto two or three axes, for example, by principal component analysis. Practitioners of numerical taxonomy have clearly illustrated the discrete nature of phenotypic clusters within many bacterial genera (9). Note that phenotype-based numerical taxonomy is ultimately much more than a method for delimiting species; it is also a venture into the natural history of a bacterial group.…”
Section: Bacterial Species As Phenotypic and Genetic Clustersmentioning
confidence: 99%
“…nov.; 2, Neisseria; 3, Kingella; 4, Eikenella; 5, Simonsiella; 6, Alysiella. Data for reference genera were obtained from Vedros (1984), Jackson & Goodman, (1984), Larkin (1989), Morse & Knapp (1991), Dewhirst et al (1993), Barrett & Sneath (1994) and Hedlund & Staley (2002). Symbols: +, positive; 2, negative; V, variable; ND, not determined.…”
mentioning
confidence: 99%